Rekonstruksi Pembelajaran Tauhid sebagai Fondasi Inovasi Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah/Madrasah - Mohammad Hosnan ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
Lately, the development of modernization has come with all its effects in human life: positive and negative. Although modernization appears to us to bring the various developments that can be utilized by humans, but on the other hand has resulted in national values and religious order kehidupanan increasingly detached from humanity. It can be seen from the rampant corruption, collusion, nepotism, terrorism, drugs, free sex and same-sex mating, immoral, and other immoral behavior. This phenomenon certainly can not be allowed to continue rampant, should be dammed one of which can be reached through education monotheism educational institutions. In the perspective of Islam, monotheism is the main foundation in building the personality of a person included in the build pradaban public life. Therefore, construction of learning pendidika monotheism in Islam or Islamic institutions must continue to be built, so that the institution can realize learning well, that is capable of transmitting knowledge and religious values on the students themselves. It is none other than as a strengthening of the identity of the students as a generation of nation and religion are responsible for building pradaban in the future. The level of knowledge and maturity of monotheism protege, will determine the future of the nation and religion.